Podejście procesowe w zarządzaniu małą firmą - Marciszewska, Anna (A Process Approach to Management of a Small Enterprise, 2009)
A processing orientation concerns not only processes happening in large enterprises, but also processes in small organizations. The interest in a process approach among small enterprises has increased, but businessmen do not have the suitable knowledge to prepare and initiate the implementation of this management method. In present market conditions, there is the need for the competence development, the adjustment to changing environment and the search for potential for development. Therefore, it is appropriate to examine this issue. The article is aimed at presenting the possibility of applying a process approach in small organizations and showing difficulties which small businesses might face. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 73-80